Pengukuran Kinerja Keuangan Menggunakan Analisis Rasio Keuangan Pada Koperasi Pegawai Republik Indonesia (KPRI) Sakti Rasa Kecamatan Barat Kabupaten Magetan - M. Hanan Habibullah; Muhammad Imron; Mutmainah Mutmainah (Universitas Merdeka Madiun, 2022)
This study aims to determine the financial performance of cooperatives using ratio analysis. The data used in this study is secondary data from 2018 to 2021. The data analysis technique uses ratio analysis techniques, the ratios used are liquidity ratios, solvency ratios and profitability ratios. The results of this study indicate that: (1) Liquidity Ratio Analysis of KPRI Sakti Rasa; (2) Solvency Ratio Analysis of KPRI Sakti Rasa; (3) Profitability Ratio Analysis of KPRI Sakti Rasa.